2021
DOI: 10.1111/1462-2920.15406
|View full text |Cite
|
Sign up to set email alerts
|

Current distribution and potential expansion of the harmful benthic dinoflagellateOstreopsiscf.siamensistowards the warming waters of the Bay of Biscay,North‐EastAtlantic

Abstract: In a future scenario of increasing temperatures in North-Atlantic waters, the risk associated with the expansion of the harmful, benthic dinoflagellate Ostreopsis cf. siamensis has to be evaluated and monitored. Microscopy observations and spatiotemporal surveys of environmental DNA (eDNA) were associated with Lagrangian particle dispersal simulations to: (i) establish the current colonization of the species in the Bay of Biscay, (ii) assess the spatial connectivity among sampling zones that explain this distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 165 publications
2
20
0
Order By: Relevance
“…Hence, the presence of cells of this ribotype in the 2021 bloom sample is not surprising, since it has been reported in the area for several years [ 66 , 67 , 70 ]. In a more recent study, a real-time polymerase chain reaction (RT-PCR) approach on many sampling sites confirmed previous observations, and this species was found in several sites between Comillas (Spain) and Biarritz (France) [ 71 ]. Furthermore, although no cells could be observed to the north of Biarritz, results from RT-PCR showed that eDNA of Ostreopsis sp.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Hence, the presence of cells of this ribotype in the 2021 bloom sample is not surprising, since it has been reported in the area for several years [ 66 , 67 , 70 ]. In a more recent study, a real-time polymerase chain reaction (RT-PCR) approach on many sampling sites confirmed previous observations, and this species was found in several sites between Comillas (Spain) and Biarritz (France) [ 71 ]. Furthermore, although no cells could be observed to the north of Biarritz, results from RT-PCR showed that eDNA of Ostreopsis sp.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, O. cf. ovata was not previously detected in this area despite a sampling in 2018 at a large geographical scale on the French Atlantic coast and the use of sensitive molecular methods in a previous study in 2018 [ 71 ]. Hence, the hypothesis of a recent introduction cannot be excluded, and the presence of this invasive dinoflagellate might cause new problems in the future, in relation to global warming.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations